REFORMASI PENDIDIKAN PESANTREN PERSPEKTIF KH. ABDUL WAHID HASYIM: KONSTRUKSI PENDIDIKAN ISLAM PROGRESIF ERA MILENIAL - Umiarso, Umiarso; Asnawan, Asnawan (Muaddib : Studi Kependidikan dan Keislaman, 2018)
Besides known as the father of the nation, KH. Abdul Wahid Hasyim is also known as a young scholar who pioneered the renewal of the education system, especially in pesantren. There are three things that AWH did in reforming the pesantren education system, is: renewal in teaching methodology, improving the quality of human resources for santri, as well as reforms in institutional and curricular areas. The text below explains the various breakthroughs done by Gus Durs father. style of educational innovation, namely: 1) Getting familiar with modern methodology; 2) Increasingly oriented towards functional education, ie open to development outside of itself; 3) Diversification of programs and activities more open and dependent with kiai is not absolute, and at the same time can equip students with various knowledge outside of religion lesson or skill that needed work world; and 4) Can serve as a community development center.